Mikrostruktur permukaan resin akrilik heat cured setelah kontak larutan cokelat - Ab Hafeez; Endanus Harijanto; Asti Meizarini (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2012)
Chocolate is one of the most popular food and beverage in the world. This caused by its good taste and anti-stress effect. Chocolate is a processed food from the seed of Theobroma cacao tree, that contain polyphenols. Chocolate beverage are consumed by everyone, as well as dentures wearers. Acrylic resins heat cured are commonly used to make dentures. This materials properties are water absorbent. Phenols chocolate solution are absorbed into the acrylic resin. This prolonged phenomenon i.e chocolate drinks, will cause changes in the physical and chemical properties of this acrylic resin. The aim of this study is to evaluate surface microstructure of the heat cured acrylic resins specimens after contact with various concentrations of chocolate solutions. Four resin acrylic specimens were processed per manufacturer’s instructions into 10x10x1,5 mm and be polished until glossy. Each specimen was submerged into different concentrations of chocolate solution (6g:200ml, 9g:200ml, 12g:200ml) and aquadest as a control for 24 days. Microstructure changes were observed using a scanning electron microscope (SEM) and energy dispersive x-ray spectroscopy (EDS). There were significant microstructural changes for all samples. The surface microstructural changes of the heat cured acrylic resins are notably higher with the increase of chocolate concentration.